Association between Multimorbidity and COVID-19 Mortality in Qatar: A Cross-Sectional Study - Khalid AbouGalala; Basant Elsayed; Mohamed Elmarasi; Mona Kotob; Reham Taha; Fardous Abbasher; Ahmed Amarah; Mariam El Hamawi; Soha S. Albayat; Jazeel Abdulmajeed; Mohamed A. H. Sallam; Maha H. M. Al-Shamali; et al. (Microbiology Research, 2023)
This study assessed the association between multimorbidity and mortality from COVID-19 in the Middle East and North Africa region, where such data are scarce. We conducted a cross-sectional study using data of all cases with COVID-19 reported to the Ministry of Public Health of Qatar from March to September 2020. Data on pre-existing comorbidities were collected using a questionnaire and multimorbidity was defined as having at least two comorbidities. Proportions of deaths were compared by comorbidity and multimorbidity status and multivariable logistic regression analyses were carried out. A total of 92,426 participants with a mean age of 37.0 years (SD 11.0) were included. Mortality due to COVID-19 was associated with gastrointestinal diseases (aOR 3.1, 95% CI 1.16–8.30), respiratory diseases (aOR 2.9, 95% CI 1.57–5.26), neurological diseases (aOR 2.6, 95% CI 1.19–5.54), diabetes (aOR 1.8, 95% CI 1.24–2.61), and CVD (aOR 1.5, 95% CI 1.03–2.22). COVID-19 mortality was strongly associated with increasing multimorbidity; one comorbidity (aOR 2.0, 95% CI 1.28–3.12), two comorbidities (aOR 2.8, 95% CI 1.79–4.38), three comorbidities (aOR 6.0, 95% 3.34–10.86) and four or more comorbidities (aOR 4.15, 95% 1.3–12.88). This study demonstrates a strong association between COVID-19 mortality and multimorbidity in Qatar.